Iron deficiency states with different types of nutrition - V. A. Kuvshinnikov; A. G. Chisty; M. Baro; A. A. Lozitskaya; S. G. Shenets; T. G. Mozzhukhina (Military Medicine, 2026)
Amon g the 38 most significant diseases on Earth, conditions associated with iron deficiency rank first. Iron deficiency anemia (IDA) is primarily related to nutrition (alimentary). Despite the high level of food availability in the Republic of Belarus and a significant reduction in the percentage of iron deficiency states (IDA and latent iron deficiency – LID) in older children and adolescents, iron deficiency states (IDS) persist in a considerable number of young children. Since the nutrition of children in the first year of life is provided either by breast milk or infant formula, the aim of this study was to compare the frequency of IDS in breastfed and formula-fed children. Mate r ials and Methods. A total of 137 children aged five months to one and a half years, treated at the 3rd City Children‘s Clinical Hospital for acute respiratory viral infections (ARVI), bronchitis, pneumonia, and otitis media, were examined. Of these, 76 were breastfed and 61 were formula-fed. A control group of children of the same age (31 children) without iron deficiency was also examined. The main indicators of the complete blood count were compared among these groups: hemoglobin content, red blood cell count, hematocrit, MCV, MCH, MCHC, and color index. Resul t s and Discussion. The obtained data revealed the following pattern: breastfed children had lower blood hemoglobin levels compared to formula-fed children and compared to the norm, while shifts toward microcytosis and hypochromia indicated iron deficiency. This is explained by the low iron content in human milk (0.35–0.4 mg/L). Conclusion . Breastfeeding is associated with a high risk of developing iron deficiency states requiring timely and adequate correction.